2019
DOI: 10.3390/resources8010022
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Local Communities towards Marula Tree (Sclerocarya birrea subsp. caffra) Conservation at the Villages of Ha-Mashau and Ha-Mashamba in Limpopo Province, South Africa

Abstract: The marula tree (Sclerocarya birrea subsp. caffra), a common species in sub-Saharan Africa, grows naturally in both protected and communal land. Although considerable research has been undertaken on these trees in southern Africa, to the authors’ knowledge, the attitudes of local communities towards the protection of marula trees, particularly in communal land, has not been researched. This study intends to fill this gap in knowledge by examining the attitudes of local people towards conservation of marula tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
(77 reference statements)
0
5
0
Order By: Relevance
“…Nevertheless, the natural resource is under considerable pressure due to the extensive clearing of woodlands for settlement and agriculture, which threaten the ecosystem services and genetic diversity of the species [85]. Despite this, a survey in southern Africa found that local communities had positive attitudes towards the conservation of marula trees and were also keen to participate in their domestication [87]. It was also clear that there is a need for more information about local management strategies [88], including its vulnerability to wildlife pressures from fruit and seed predation, especially from elephants [89].…”
Section: Sclerocarya Birrea (Marula) 421 Ethnobotany Uses and Natural...mentioning
confidence: 99%
“…Nevertheless, the natural resource is under considerable pressure due to the extensive clearing of woodlands for settlement and agriculture, which threaten the ecosystem services and genetic diversity of the species [85]. Despite this, a survey in southern Africa found that local communities had positive attitudes towards the conservation of marula trees and were also keen to participate in their domestication [87]. It was also clear that there is a need for more information about local management strategies [88], including its vulnerability to wildlife pressures from fruit and seed predation, especially from elephants [89].…”
Section: Sclerocarya Birrea (Marula) 421 Ethnobotany Uses and Natural...mentioning
confidence: 99%
“…Other studies have revealed that the strong cultural attachment to some forests has made it difficult for local people to accept some conservation efforts, especially those limiting their access to the forest (Nkemnyi et al, 2013). Consequently, cultural value can be a weak and inadequate value system for conservation (Jones et al, 2008;Sinthumule & Mashau, 2019).…”
Section: Relational Value Orientationmentioning
confidence: 99%
“…Marula fruit juice has been investigated for its exceptionally high quantity of vitamin C content, reported to be about 62–400 mg per 100 g in fresh juice (Hiwilepo‐van Hal et al, 2012). Due to its high vitamin C content, marula fruit could act as an alternative source of vitamin C for individuals seeking to variegate from market‐driven fruits such as citrus fruits, apples, grapes, and guabiroba fruit (Grutzmann Arcari et al, 2020; Sinthumule & Mashau, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…
Marula fruit (Sclerocarya birrea subsp. Caffra) is to a great extent the most utilized indigenous wild fruit for local rural communities of southern African communities (Sinthumule & Mashau, 2019).The fruits are consumed in their raw form or transformed into byproducts such as jams, beverages, concentrates, and the popular fermented alcoholic beverage known as Amarula (Dlamini, 2011;Schulze-Kaysers et al, 2015). Marula fruit juice has been investigated for its exceptionally high quantity of vitamin C content, reported to be about 62-400 mg per 100 g in fresh juice (Hiwilepo-van Hal et al, 2012).
…”
mentioning
confidence: 99%
See 1 more Smart Citation